The Disconcerting Pyramids of Poverty and Inequality of Sub-Saharan Africa - Lopes, Paulo (IMF Working Papers; Working Paper, 2005)
Poverty and inequality in Sub-Saharan Africa (SSA) should not be ascertained only on the basis of scarce and unreliable income distribution statistics, but should also take into account social conditions. Recent, widely disseminated claims that poverty and inequality have increased over the past 30 years are based on regional income estimates with falling medians and rising upper variances over that period. Graphically, this translates into pyramid-shaped income distributions that, perversely, shift to the left and widen over time. However, during the same period social indicators improved significantly (if insufficiently), and we argue in this paper that such a trend represents progress with social equity in SSA. This point is illustrated through the configuration of alternative "social pyramids" that move for most of the last 30 years in the right direction. However, more recently, social indicators are being set back by the HIV/AIDS pandemic, which will generate greater and more dehumanizing poverty in the years ahead even if meaningful economic growth is achieved. As underscored by the multiplicity of "pyramid" representations, poverty and inequality time trends in SSA can thus best be described as disconcerting in that they remain arguably illusive and definitely disturbing.